2002
DOI: 10.1016/s1010-7940(02)00260-9
|View full text |Cite
|
Sign up to set email alerts
|

The Jarvik 2000 Heart. Clinical validation of the intraventricular position

Abstract: The Jarvik 2000 is an effective user-friendly LVAD which allows early discharge from hospital. The intraventricular position has distinct advantages especially through absence of an inflow cannula. Synergy develops between the LVAD and native left ventricle. Early experience suggests that this may be a realistic LVAD to treat heart failure routinely in the outpatient setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 7 publications
1
45
0
Order By: Relevance
“…Two case series studies evaluating the Jarvik 2000 LVAD were judged to be methodologically weak, [94][95][96][97][98][99][100] with poor reporting of the selection criteria for participants and the methods of data collection (Appendix 16). Outcome assessment was not blinded, providing the opportunity for ascertainment bias.…”
Section: Jarvikmentioning
confidence: 99%
See 4 more Smart Citations
“…Two case series studies evaluating the Jarvik 2000 LVAD were judged to be methodologically weak, [94][95][96][97][98][99][100] with poor reporting of the selection criteria for participants and the methods of data collection (Appendix 16). Outcome assessment was not blinded, providing the opportunity for ascertainment bias.…”
Section: Jarvikmentioning
confidence: 99%
“…One study of the Jarvik 2000 LVAD focused on males (66%) with a mean age of 47 years and suffering from ischaemic aetiology, 94 whereas in the other case study patient ages ranged from 30 to 70 years, 73% were male and 50% suffered from dilated cardiomyopathy and 50% from ischaemic cardiomyopathy. [94][95][96][97][98][99][100] The patients in the MicroMed DeBakey studies range in age from 33 to 65 years and were predominantly male. The case studies of the Thoratec LVAD each reported male patients.…”
Section: Generalisabilitymentioning
confidence: 99%
See 3 more Smart Citations